A Meta-Analysis of 13 Randomized Trials on Traditional Chinese Medicine as Adjunctive Therapy for COVID-19: Novel Insights into Lianhua Qingwen. (30th October 2022) - Lei, Yi; Guan, Huizhen; Xin, Wenqiang; Yang, Bi-Cheng
Abstract : The efficacy and safety of traditional Chinese medicine (TCM) paired with western medicine in the treatment of patients with COVID-19 remains controversial. This meta-analysis was performed to identify the effects of TCM. Seven electronic databases were reviewed from the inception of these databases to 30 June 2022. A quality assessment of the included studies was performed with the Cochrane Collaboration's tool to provide a score of high, unclear, or low risk of bias. The standard software program (Stata, version 12.0, statistical software) was used for endpoint analyses. A total of 13 RCTs involving 1398 patients conducted in China were included. The cross-sectional data from various studies were plotted, and the results illustrated that the statistically higher rates of total effectiveness (RR, 1.357; 95% CI, 1.259 to 1.464; P < 0.001 ), improvement of chest CT (RR, 1.249; 95% CI, 1.143 to 1.356; P < 0.001 ), and cough improvement (RR, 1.228; 95% CI, 1.057 to 1.570; P = 0.012 ) and a lower incidence of conversion to severe cases (RR, 0.408; 95% CI, 0.275 to 0.605; P < 0.001 ) were demonstrated in the TCM group than that of the control group. Of note, the subgroup on specific TCM of Lianhua Qingwen (LQ) revealed that the experiment group was associated with a higher rate of total effectiveness (RR, 1.248; 95% CI, 1.136 to 1.371; P < 0.001 ) and improvement of chest CT (RR, 1.226; 95% CI, 1.110 to 1.356; P < 0.001 ) and a lower rate of conversion to severe cases (RR, 0.469; 95% CI, 0.311 to 0.707; P < 0.001 ). However, there was no significant difference in fever improvement (RD, 0.110; 95% CI, -0.063 to 0.283; P = 0.213 ). The findings of this meta-analysis suggest that TCM combined with western medicine is more effective in treating COVID-19 via relieving symptoms, promoting patients' recovery, and cutting the rate of patients developing into severe conditions. However, given the relevant possible biases in our study, adequately powered and better-designed studies with long-term follow-up are required to reach a firmer conclusion.